High dose methotrexate in the treatment of children with acute lymphoblastic leukemia - Johannes Bondan Lukito (Indonesian Pediatric Society, 2007)
Background It has been claimed that around 70% of childhoodacute lymphoblastic leukemia (ALL) can be cured. One of theimportant role is high dose methotrexate (HDMTX) administrationduring the consolidation therapy.Objective To determine the safety and effectiveness of HDMTXin children with ALL.Methods We reviewed patients with ALL in Pantai Indah KapukHospital, Jakarta during the period August 2000 through July 2005with observation time run through September 2006. Only patientswith normal kidney function were allowed to have HDMTX. Besidesgood hydration and alkalinization, patients were supported with goodhygiene (mouth, skin and anal area). MTX was given in loadingdose of 10% from the total dose in Â½ hour and the rest 23Â½ hours for90%. Leucovorin rescue was started 12 hours after discontinuationof 24 hour MTX IV infusion. Leucovorin was given until the MTXconcentration reached 0.1 uM/L. Patients were stratified to low,intermediate and high risk groups; 2 gram/m 2 was given to low riskgroup and 5 gram/m2 to intermediate and high risk groups.Results There were 20 patients eligible for study. All methotrexatesteady-state plasma concentrations (MTX Cp ss ) were above 16 uM/L, and steady state concentration in CSF was always below 0.5 uM/L for 2 gram/m 2 and above 0.5 uM/L for 5 gram/m 2 doses. All 20cases went through the procedure with only mild side effects i. e,mild mucositis, anal furuncle and diarrhea, which recovered 2 weekslater. Only 1 high risk case with initial WBC 612X10 9 /L, succumbedafter he went through the HDMTX program smoothly and relapsedsubsequently during reinduction phase.Conclusion HDMTX can be given safely to ALL patients with normalkidney function with good supportive care. Five gram/m 2 HDMTXeffectively treat the minor disease and/or prevent CNS and testicularleukemia. This study has also given an impression that HDMTXmay increase event-free survival.